Pemanfaatan Cryptocurrency Dalam Tindak Pidana Pencucian Uang - Nadia Wulandari Rotty; Anggita Cahyani; Daffa Khalisha Nabila; Rachmah Fidiastuti; Regentio Candrika Komala Dewa (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Money laundering as one of the extraordinary crimes has changed due to technological developments and advances. Virtual money or cryptocurrency as a form of digital transaction tool circulating in the cyber world has the potential to become a target for perpetrators of money laundering crimes. The occurrence of money laundering crimes through cryptocurrency has the potential to complicate the process of investigation, prosecution, and execution of Money Laundering Crime cases so that it requires special attention by the government and all levels of society. The purpose of this study is to determine the potential use of cryptocurrency as a means of money laundering crimes and to determine the urgency of regulation and handling of money laundering crimes using cryptocurrency. This research uses normative legal research methods. The results of this study assess that the use of cryptocurrency as a means of money laundering requires strict supervision by law enforcement officials and a binding legal basis regarding the use of cryptocurrency as a means of payment in Indonesia so as to minimize the occurrence of a crime, especially money laundering by irresponsible parties.